KEBIJAKAN HUKUM PIDANA PELECEHAN SEKSUAL SECARA VERBAL DALAM HUKUM PIDANA INDONESIA - Luthfi, Saskia Salsabilla; R, Mukhlis; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Sexual violence is increasingly happening, both in public places and inoffices. Problems Sexual violence is a form of human rights violations, crimesagainst human dignity, and forms of discrimination. According to his definition,sexual violence is any form of behavior that has a sexual content that is carriedout by a person or a number of people but is not liked and not expected by theperson who is being targeted so that it causes negative consequences, such as:shame, offence, humiliation, anger, loss of self-esteem, loss of holiness and so on.From the background of the problem above, the purpose of writing this thesis:first, to find out how to regulate verbal sexual harassment in Indonesian CriminalLaw. Second, to find out how to regulate verbal sexual harassment in severalcountries. Third, to find out how to regulate verbal sexual harassment inIndonesia in the future.The author conducts research using normative juridical methods. Thesource of data used is library research, namely in order to obtain secondary datathrough documentary studies, namely by studying and analyzing comparativelydescriptive laws and regulations with theories that have a relationship with theproblems studied.From the results of the study, there are three main things that can beconcluded: First, the regulation of verbal sexual harassment in IndonesianCriminal Law is seen from the Criminal Code and the Criminal Procedure Code,the regulation of verbal sexual harassment in several countries such as SexualOff. ences Act is used by 4 countries, namely Barbados, England, Bahamas andIndia, Third, the regulation of verbal sexual harassment in Indonesia in the futurewhich refers to the Law on the Elimination of Sexual ViolenceKeywords : Verbal Sexual Harassment – Verbal Sexual Arrangements -Indonesian Criminal Law